Effect of Soaking Time of Indian Camphorweed (Pluchea Indica L.) Leaf Extract on the Growth of Seaweed (Kappaphycus alvarezii) - Musa Laylatul Qodriyah; Aslan La Ode Muhammad; Yusnaini Yusnaini; Ruslaini Ruslaini; Kurnia Agus; Balubi Abdul Muis (BIO Web of Conferences)
The growth of Kappaphycus alvarezii can be enhanced with biofertilizers. This study aimed to determine the optimal soaking time for K. alvarezii in camphor leaf extract (Pluchea indica L.) to improve growth. This study was conducted over 45 days, from May to July 2024, in the coastal waters of Rahia village, Central Buton district, Southeast Sulawesi. The study included four different soaking times (0, 6, 9 and 12 hours) as treatments with 12 replications. Observed variables included the daily growth rate (DGR), dry weight to wet weight ratio (DW: WW), clean anhydrous weed (CAW) content, as well as the presence of epiphytes and diseases. The highest DGR, which tended to be significantly different (P< 0.05), was observed in the 9-hour soaking times, ranging from 4.45% to 10.69% per day, while the lowest was in the 0-hour treatment, at 3.66% to 8.48% per day. No significant differences (P> 0.05) were found for DW: WW ratio and CAW content. Although Ulva lactuca were detected, no diseases or epiphytes were found in any extract treatments. A 9-hour soaking period in camphorweed leaf extract can effectively support the growth of K. alvarezii growth.